Therapeutic approaches for the treatment of genetic and acquired cardiovascular calcification - O’Brien, Kevin; Husson, Hervé; Sabbagh, Yves (Frontiers in Cardiovascular Medicine, 2025)
Vascular calcification, the deposition of calcium-phosphate crystals in the vasculature, occurs through a complex interplay between cellular processes and biochemical factors that are yet to be entirely defined. Vascular calcification results in stiffening of the arteries and ultimately cardiovascular complications. Deposition can occur either in the intima or media layers of a vasculature through discrete mechanisms and underlying pathologies. Medial calcification, the subject of this review, occurs in a specific set of pathologies including genetic disorders, diabetes, and chronic kidney disease. There are currently no approved therapies for prevention of medial vascular calcification leaving this an active area of unmet therapeutic need. One of the key molecule involved in preventing vascular calcification is pyrophosphate (PPi), long known as a potent inhibitor of mineralization. Many therapeutic avenues, both historical and current, have focused on increasing the plasma concentration of PPi. This can be accomplished by direct PPi supplementation or by use of bisphosphonates, acting as non-hydrolysable PPi analogs, though both approaches have limitations. Newer therapies utilize recombinant ENPP1, which generates PPi by hydrolysis of endogenous ATP, an approach which is currently being evaluated in clinical trials. Another approach to elevate plasma PPi concentration is by preventing enzymatic degradation of PPi through inhibition of alkaline phosphatase. Alternatively, chelation of either phosphate or calcium, the key constituent minerals of calcification, using phosphate binders represent other approaches as well as the use of magnesium and vitamin K supplementation. This review will first briefly discuss the pathophysiology of medial vascular calcification and describe the disease conditions involved before surveying the different therapeutic interventions evaluated to address the medial vascular calcification in the setting of genetic diseases as well as chronic diseases. We will present a bench to bedside view of development discussing therapeutic evidence in animal models, clinical trials and their relevance and applicability to clinical development.